Integration of technology-based outcome measures in clinical trials of Parkinson and other neurodegenerative diseases - Artusi, Carlo Alberto (Parkinsonism Relat Disord, 2017)
INTRODUCTION: We sought to review the landscape of past, present, and future use of technology-based outcome measures (TOMs) in clinical trials of neurodegenerative disorders. METHODS: We systematically reviewed PubMed and ClinicalTrials.gov for published and ongoing clinical trials in neurodegenerative disorders employing TOMs. In addition, medical directors of selected pharmaceutical companies were surveyed on their companies’ ongoing efforts and future plans to integrate TOMs in clinical trials as primary, secondary, or exploratory endpoints. RESULTS: We identified 164 published clinical trials indexed in PubMed that used TOMs as outcome measures in Parkinson disease (n = 132) or other neurodegenerative disorders (n = 32). The ClinicalTrials.gov search yielded 42 clinical trials using TOMs, representing 2.7% of ongoing trials. Sensor-based technology accounted for over 75% of TOMs applied. Gait and physical activity were the most common targeted domains. Within the next 5 years, 83% of surveyed pharmaceutical companies engaged in neurodegenerative disorders plan to deploy TOMs in clinical trials. CONCLUSION: Although promising, TOMs are underutilized in clinical trials of neurodegenerative disorders. Validating relevant endpoints, standardizing measures and procedures, establishing a single platform for integration of data and algorithms from different devices, and facilitating regulatory approvals should advance TOMs integration into clinical trials.